2015
DOI: 10.3310/hsdr03270
|View full text |Cite
|
Sign up to set email alerts
|

Mobilising knowledge to improve UK health care: learning from other countries and other sectors – a multimethod mapping study

Abstract: BackgroundThe past two decades have seen rich conceptual development and a wide variety of practical initiatives around research use or ‘knowledge mobilisation’, but so far there has been little systematic effort to map, conceptualise and learn from these initiatives, or to investigate the degree to which they are underpinned by contemporary thinking as set out in the literature. This gap is particularly apparent when looking at knowledge mobilisation at the ‘macro’ level, that is the strategies and activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
176
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(189 citation statements)
references
References 160 publications
2
176
0
3
Order By: Relevance
“…In contrast, advocates of co-production have enthusiastically developed theories and frameworks but have been less successful to date in developing workable models which can be used by practitioners. 4 Underlying this problem is the deeply embedded distinction between the academic and practitioner communities. For this reason, a possible solution lies in the application of a research paradigm which brings the two communities together.…”
Section: From Theory To Practice: Participatory Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, advocates of co-production have enthusiastically developed theories and frameworks but have been less successful to date in developing workable models which can be used by practitioners. 4 Underlying this problem is the deeply embedded distinction between the academic and practitioner communities. For this reason, a possible solution lies in the application of a research paradigm which brings the two communities together.…”
Section: From Theory To Practice: Participatory Researchmentioning
confidence: 99%
“…[2][3][4][5] Here, for research to have impact, both knowledge producers and users need to be involved in its creation and its application. A strong emphasis is placed on co-production, the development of positive relationships, effective systems and a conducive organisational context.…”
Section: Mobilising Knowledgementioning
confidence: 99%
“…13 There is both confusion of terms and confusion in the meaning of terms. 90 Knowledge translation, for example, can refer to the job of 'translating' lengthy and complex research reports into digests more suitable for busy practitioners; the translation of knowledge into action or practice arising from collaboration between researchers and practitioners; 82,91 or the 'transfer' of research from one group to another with little interpretation or amendment. 7 Transfer needs to be understood in relation to definitions of knowledge and different models of KIT will prescribe the role for people and organisations responsible for enabling it.…”
Section: Transfermentioning
confidence: 99%
“…94,99,100 Davies et al 90 suggested six archetypes of knowledge mobiliser: knowledge product pushers; brokers and intermediaries of their own research; brokers and intermediaries of wider research; evidence advocates (champions for evidence-informed practice); network fosterers (developing new ones and enhancing existing ones); and advancers of knowledge mobilisation (enhancing knowledge about KIT work). Within these archetypes, agents carry out three broad overlapping roles: developing and sharing research-based products, brokering and implementation.…”
mentioning
confidence: 99%
“…The St Andrews team recently hosted another workshop, reviewing what we now know about Knowledge Mobilisation and how it is being approached by research agencies such as funders, think tanks, and evidence centres (Davies et al 2014). We were all in attendance and one thing we were struck by, both in the presentation of the research and the discussion that followed, was that in some ways little has changed.…”
Section: Whose Evidence Is It Anyway?mentioning
confidence: 99%